Faktor Yang Mempengaruhi Profitabilitas dan Nilai Perusahaan Sektor Makanan dan Minuman - Tan Monica; Sunarto Sunarto (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The purpose of this study is to analyze and explain the effect of good corporate governance and capital structure on profitability, to analyze and explain the effect of good corporate governance, capital structure and profitability on firm value. The type of research used in this study is explanatory research with a quantitative approach, namely by testing the comparative causal relationship of the measured research variables. The results of this study are good corporate governance has no significant effect on profitability, capital structure has a positive effect on profitability, good corporate governance, capital structure and profitability have a positive effect on firm value, profitability does not mediate the effect of good corporate governance on firm value and profitability mediates the effect capital structure on firm value